2020
DOI: 10.3390/molecules25112500
|View full text |Cite
|
Sign up to set email alerts
|

New Methyl Threonolactones and Pyroglutamates of Spilanthes acmella (L.) L. and Their Bone Formation Activities

Abstract: In our continuing research for bioactive constituents from natural resources, a new methyl threonolactone glucopyranoside (1), a new methyl threonolactone fructofuranoside (2), 2 new pyroglutamates (3 and 4), and 10 known compounds (5–14) were isolated from the whole plant of Spilanthes acmella (L.) L. The structures of these compounds were determined based on various spectroscopic and chemical analyses. All of the isolated compounds were evaluated on bone formation parameters, such as ALP (alkaline phosphatas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Spilanthol and other alkyl amides present in B. acmella extract also contributed significantly to its anti-inflammatory ( Sharma et al, 2011 ; Bakondi et al, 2019 ) and antioxidant ( Abeysiri et al, 2013 ; Sharma and Arumugam, 2021 ) activities. A recent study also reported that components in B. acmella extract such as 1,3-butanediol 3-pyroglutamate, 2-deoxy-d-ribono-1,4-lactone, methyl pyroglutamate, ampelopsisionoside, icariside B1, bezyl-α-1-arabinopyranosyl-(1,6)-β-d-glucopyranoside ( Widyowati et al, 2020a ), methyl threonolactones, and pyroglutamates contributed to its ALP activity and mineralization of osteoblast MC3T3-E1 cells ( Widyowati et al, 2020b ).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Spilanthol and other alkyl amides present in B. acmella extract also contributed significantly to its anti-inflammatory ( Sharma et al, 2011 ; Bakondi et al, 2019 ) and antioxidant ( Abeysiri et al, 2013 ; Sharma and Arumugam, 2021 ) activities. A recent study also reported that components in B. acmella extract such as 1,3-butanediol 3-pyroglutamate, 2-deoxy-d-ribono-1,4-lactone, methyl pyroglutamate, ampelopsisionoside, icariside B1, bezyl-α-1-arabinopyranosyl-(1,6)-β-d-glucopyranoside ( Widyowati et al, 2020a ), methyl threonolactones, and pyroglutamates contributed to its ALP activity and mineralization of osteoblast MC3T3-E1 cells ( Widyowati et al, 2020b ).…”
Section: Introductionmentioning
confidence: 92%
“…In addition, the use of B. acmella extracts followed by exercise activity on mice increased the bone formation rate of mouse femur trabecular ( Laswati et al, 2015 ). Methyl threonolactone glucopyranoside group, methyl threonolactonefructofuranoside, methyl pyroglutamates, and amine cell derivatives isolated from B. acmella methanol extracts were recently demonstrated to significantly increase the ALP and mineralization activities of osteoblast cells ( Widyowati et al, 2020a ; Widyowati et al, 2020b ).…”
Section: Introductionmentioning
confidence: 99%
“…Twenty-two known compounds were identified as quercetin-3- O - β -D-rhamnopyranoside ( 4 ) [ 17 ], 6-methoxy-naringenin ( 5 ) [ 18 ], 6-methoxy-kaempferol ( 6 ) [ 19 ], kaempferol ( 7 ) [ 20 ], apigenin ( 8 ) [ 21 ], abscisic acid ( 9 ) [ 22 ], (+)-dehydrovomifoliol ( 10 ) [ 23 ], grasshopper ketone ( 11 ) [ 24 ], roseoside ( 12 ) [ 25 ], citroside A ( 13 ) [ 23 ], 4′-(6-amino-9 H -purin-9-yl)pentan-2′-one ( 14 ) [ 26 ], seco-( S -Pro- R -Val) (1 5 ) [ 27 ], cyclo-( L -Pro- L -Ala) ( 16 ) [ 28 ], 3-methoxyl-1 H -pyrrole ( 17 ) [ 29 ], cyclo-(Ala-Val) ( 18 ) [ 30 ], indole-3-carboxyl- β -D-glucopyranoside ( 19 ) [ 31 ], uridine ( 20 ) [ 32 ], thymidine ( 21 ) [ 33 ], adenosine ( 22 ) [ 34 ], hypoxanthine ( 23 ) [ 35 ], aurantiamide acetate ( 24 ) [ 36 ], and L -pyroglutamic acid methyl ester ( 25 ) [ 37 ].…”
Section: Resultsmentioning
confidence: 99%